Building Fintech Ecosystems: Regulatory Sandboxes, Innovation Hubs and Beyond - Ross P. Buckley; Dougles Arner; Robin Veidt; Dirk Zetzsche (Washington University Journal of Law & Policy, 2020)
Around the world, regulators and policymakers are working to support the development of financial technology (FinTech) ecosystems. As one example, more than fifty jurisdictions have now established or announced “financial regulatory sandboxes.” Others have announced or established “innovation hubs,” sometimes incorporating a regulatory sandbox as one element. This article argues that innovation hubs provide all the benefits that the policy discussion associates with regulatory sandboxes, while avoiding most downsides of regulatory sandboxes, and that many benefits typically attributed to sandboxes are the result of inconsistent terminology, and actually accrue from the work of innovation hubs. The paper presents, as the first contribution of its kind, data on regulatory sandboxes and innovation hubs and argues that the data so far available on sandboxes does not justify the statement that regulatory sandboxes are the most effective approach to building FinTech ecosystems. Given that regulatory sandboxes require significant financial contributions, sometimes new legislation, and intense regulatory risk management, and that they do not work as well on a stand-alone basis (i.e. without an innovation hub), while innovation hubs alone can provide more significant benefits in support the development of a FinTech ecosystem, regulators should focus their resources on developing effective innovation hubs, including, in appropriate cases, a sandbox as one possible element.
Keywords: fintech; financial; financial services; financial technology; finance; finance law; law; technology law; regulatory sandbox; innovation hub